Internalisasi Islam wasathiyyah di pondok pesantren Nurul Hidayah kabupaten Bengkalis - Mardhotillah, Nadana; Junaidi, Junaidi; Milani, Risna (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
As traditional Islamic educational institutions, Islamic boarding schools have a strategic role in shaping the young generation’s religious character and noble morals. This study examines the internalization of moderate Islamic values ​​at pondok pesantren (Islamic boarding school) Nurul Hidayah Modern and the resilience of this Islamic boarding school in facing the challenges of religious-based radicalism. This study uses a descriptive qualitative approach with interviews, observation, and documentation. The study finds that the internalization of wasathiyyah values at pondok pesantren Nurul Hidayah (PPNH) occurs through teaching, habituation, and exemplary practices, fostering tolerance, balance, non-violence, and respect for local culture. These values are cognitively transmitted and practiced in students’ daily lives. The pesantren also demonstrates resilience against religious-based radicalism by integrating moderate curricula, strengthening national values, and upholding the charismatic leadership of the kiai. Hence, PPNH is both a center of character formation and a cultural pillar against radicalism.